2016
DOI: 10.1051/0004-6361/201628969
|View full text |Cite
|
Sign up to set email alerts
|

Stellar systems in the direction of the Hickson Compact Group 44

Abstract: Context. In spite of the numerous studies of low-luminosity galaxies in different environments, there is still no consensus about their formation scenario. In particular, a large number of galaxies displaying extremely low-surface brightnesses have been detected in the last year, and the nature of these objects is under discussion. Aims. In this paper we report the detection of two extended low-surface brightness (LSB) objects (µ eff g ′ ≃ 27 mag) found, in projection, next to NGC 3193 and in the zone of the H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Since the recent revival of the UDGs in Coma (van Dokkum et al 2015;Koda et al 2015), the number of the known UDGs keeps increasing. The UDGs are found from the lowdensity regions to the high density environments such as galaxy clusters (Mihos et al 2015;Yagi et al 2016;Smith Castelli et al 2016;van der Burg et al 2016;Martin et al 2016;Merritt et al 2016;Bellazzini et al 2017;Román & Trujillo 2017a,b).…”
mentioning
confidence: 99%
“…Since the recent revival of the UDGs in Coma (van Dokkum et al 2015;Koda et al 2015), the number of the known UDGs keeps increasing. The UDGs are found from the lowdensity regions to the high density environments such as galaxy clusters (Mihos et al 2015;Yagi et al 2016;Smith Castelli et al 2016;van der Burg et al 2016;Martin et al 2016;Merritt et al 2016;Bellazzini et al 2017;Román & Trujillo 2017a,b).…”
mentioning
confidence: 99%
“…We want to expand such discussion further and explore which kind of structures (groups or clusters) are more favorable for the formation of UDGs. Initially, clusters were considered the natural place for finding UDGs; however, there is increasing evidence (first noted by Román & Trujillo (2017) and recently by Merritt et al (2016); see also: Ordenes-Briceño et al (2016);Smith Castelli et al (2016)) that UDGs are also found outside clusters. The existence of UDGs in the field has also been motivated theoretically by Di Cintio et al (2017).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…But UDGs also appear to exist outside of clusters. Martínez-Delgado et al (2016) report the discovery of a UDG in the Pisces-Perseus Filament, and Merritt et al (2016) andSmith Castelli et al (2016) report the discovery of UDGs in group environments. Román & Trujillo (2017a) statistically estimate the distribution of UDGs around Abell 168, and suggest that more than 50% of UDGs could exist outside of the cluster environment.…”
Section: Introductionmentioning
confidence: 99%